Inquiry into the Conceptual Dimensions of Project Portfolio Management - Pedro Bruno de Souza; Jorge Carneiro; Rodrigo Bandeira-de-Mello (BBR: Brazilian Business Review)
Although much has been written about how to manage individual projects, there is still little guidance on how to evaluate the “quality” of project portfolio management itself, that is, the degree of “accomplishment” of the process by which the project portfolio is formed and run. This study addresses this gap by employing a q ualitative approach to uncover managerial perceptions about what is encompassed by project portfolio management and how the this construct should be evaluated. By building from a review of the scant literature on project portfolio management , conversations with expert scholars on project management, interpretations provided by managers, and theoretical reflection by the authors of this study, it was possible to identify main aspects that seem to tap how the degree of “accomplishment” of project portfolio ma nagement can be conceptually defined and operationally measured.